2022
DOI: 10.5937/topola2209031v
|View full text |Cite
|
Sign up to set email alerts
|

The influence of powdery mildew on chlorophyll a fluorescence and stomatal characteristics of pedunculate oak (Quercus robur L.)

Abstract: Oak powdery mildew (Erysiphe alphitoides (Griffon and Maubl.) U. Braun and S. Takam.)) is one of the most common foliar pathogenic organism of oaks, exploiting harmful effects, particularly on young seedlings. To assess and evaluate these negative effects, an experiment was conducted under semi-controlled conditions with 20 one-year-old seedlings of Quercus robur L. infected with E. alphitoides, half of them showing 50% of leaf coverage by epiphytic mycelia and the other half a coverage of 75%. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Trees in urban surroundings have to adapt to significantly changed environments [8][9][10]. On the other hand, ongoing climate change evidently negatively affects whole vegetation and, in synergy with intensive drought periods, significantly reduces their growth and physiological properties, as well as vitality status [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Trees in urban surroundings have to adapt to significantly changed environments [8][9][10]. On the other hand, ongoing climate change evidently negatively affects whole vegetation and, in synergy with intensive drought periods, significantly reduces their growth and physiological properties, as well as vitality status [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…These areas are among the primary supporters of urban region's sustainability, people's wellness, and urban life quality, considered to provide social, ecological, and economic benefits [1,2]. The increased attention directed to green infrastructure (i.e., the employment of plants in cities) arises from the numerous ecosystem services they provide, which support and enrich human life [3,4]. The numerous supported or enabled vegetation-based benefits include the production of food, regulation of noise and air pollution, the urban heat island effect reduction, control of biogeochemical cycling, flood mitigation, biodiversity maintenance, rendering the rest and recreation of city residents (beneficial 2 for physical health, socialization, stress level), as well as increasing of the metropolitan property values [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Significance of the recent study of Trudić and Avramidou et al (2021a) reflects in two aspects: it tackled genetic diversity of the same population used in this study and it indicated rich heterozygosity and stable genetic diversity. In addition, biochemical, physiological and morphological diversity of Q. robur from Serbia were assessed, under open, controlled and stressful conditions, tracking various biochemical and morphological traits and parameters (Stojnić et al, 2019;Pilipović et al, 2020;Vaštag et al, 2020;Vaštag et al, 2022, Kebert et al, 2022a, 2022b, 2022c. These stu-dies gave an immense contribution to the understanding of genetical and physiological foundations of pedunculate oak diversity on the territory of Serbia, especially in terms of understanding possible links of used morphometrics and physiological markers to differ oak genetic structure and its drought stress resilience capacity.…”
Section: Introduction Uvodmentioning
confidence: 99%